Representing Chemical Events by using Mathematical Notation from Pre-conceptual Schemas (2019)
Events are occurrences that happen in systems. Events can be chemical, which are natural phenomena studied from the chemical field. Such events modify chemical composition of substances when they are combined with other substances. Chemical experts represent such events by using scientific models, which are used for describing and recognizing behavior of the real world. Such models are integrated into scientific software systems. However, software engineering models lack mathematical notation for representing chemical events. Hence, in this paper we propose a chemical event representation by using mathematical notation from pre-conceptual schemas. Such schemas are used for representing events in scientific software domains. The proposed representation allows for analyzing chemical events from software engineering in order to produce scientific software systems from chemical field.